Does Dynastic Prohibition Improve Democracy? - Cruz, Jan Frederick (Archīum Ateneo, 2015)
In aid of legislation on a possible anti-dynasty law in the Philippines, this paper probes the different aspects of dynastic prohibition, drawing in part from international experiences on similarly-minded laws and policies in other democracies. As a first step, it reviews the related literature, particularly on nepotism and political dynasties which are similar in some aspects but quite distinct concepts. It also discusses the arguments surrounding the dynastic prohibition in the Philippine Constitution, drawing on historical accounts of the 1986 Constitutional Commission's work. In order to help operationalize this, the paper then provides an overview of various definitions of "political dynasty" based on legislative bills and constitutions of other countries. Finally it undertakes an empirical analysis of whether these laws appear to be associated with further democratization of these countries that introduced these dynastic restrictions.